2019
DOI: 10.1111/apt.15371
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world short‐term effectiveness of ustekinumab in 305 patients with Crohn’s disease: results from the ENEIDA registry

Abstract: Summary Background There are limited data of ustekinumab administered according to the doses recommended in the UNITI studies. Aim To assess the real‐world, short‐term effectiveness of ustekinumab in refractory Crohn's disease (CD) Methods Multicentre study of CD patients starting ustekinumab after June 2017 at the recommend dose (260, 390 or 520 mg based on weight ~6 mg/kg IV week 0 and 90 mg subcutaneously week 8). Values for Harvey‐Bradshaw Index (HBI), C‐reactive protein (CRP) and faecal calprotectin (FC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 36 publications
13
82
1
Order By: Relevance
“…Several studies have provided real-world data on the safety and efficacy of UST. Due to its rather recent approval, most studies evaluate short-term effectiveness [7] only, are retrospective, or do not include the intravenous induction regimen [8,9]. Only a few studies provide insight into long-term effectiveness [10,11] or are prospectively conducted [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided real-world data on the safety and efficacy of UST. Due to its rather recent approval, most studies evaluate short-term effectiveness [7] only, are retrospective, or do not include the intravenous induction regimen [8,9]. Only a few studies provide insight into long-term effectiveness [10,11] or are prospectively conducted [12].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the decrease of CRP, FC and HBI were more pronounced after intravenous dosing (week 8) than after subcutaneous dosing (week 14), probably due to a lack of drug dose . A recent study demonstrated an association between increased FC beyond week 8 and unsatisfactory endoscopy outcomes due to lower levels of ustekinumab .…”
mentioning
confidence: 95%
“…We appreciate Drs. Frasca and Cheifetz’ editorial on our recent paper . Due to the recent approval of ustekinumab, there are few studies about its real‐world effectiveness in Crohn's disease (CD) patients treated with recommended doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Iborra et al assessed the short‐term effectiveness of ustekinumab in 305 patients with Crohn's disease. The information was obtained from the ENEIDA database .…”
mentioning
confidence: 99%